High-resistance inspiratory muscle strength training: a promising strategy for improving vascular health in chronic kidney disease - Lapierre-Nguyen, Stephanie; Buffington, Tyler; Chonchol, Michel; Nowak, Kristen L. (Frontiers in Physiology, 2025)
Patients with chronic kidney disease (CKD) demonstrate accelerated vascular aging which contributes to an increased risk of cardiovascular disease (CVD). Impaired vascular health in CKD is characterized by both functional and structural alterations to the vasculature including hypertension, arterial stiffness, vascular endothelial dysfunction, and autonomic dysfunction. These detriments persist despite pharmacological intervention. Habitual aerobic exercise can be protective of vascular health; however, the feasibility in patients with CKD is low due to numerous barriers to exercise. In this perspective we emphasize the need for novel and non-pharmacological strategies that can rescue vascular health and reduce the development of CVD in patients with CKD, explain the unique barriers to aerobic exercise in CKD, present a novel physical training intervention—high-resistance inspiratory muscle strength training (IMST) that addresses the barriers to exercise, and provide our opinion on why this lifestyle intervention may be particularly efficacious for patients with CKD.